Characterization of an ADAMTS-5-mediated cleavage site in aggrecan in OSM-stimulated bovine cartilage. - Durigova, M; Soucy, P; Fushimi, K; Nagase, H; Mort, J; Roughley, P (2008)
OBJECTIVE: In a previous study, we identified a 50-kDa G3-containing aggrecan degradation product in bovine cartilage, released from the tissue after interleukin-1 (IL-1) stimulation in the presence of oncostatin M (OSM). Our objective was to purify, determine the N-terminal sequence of this fragment and verify whether this cleavage could be attributed to a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-4 and ADAMTS-5 action in vitro. METHODS: Collected media from bovine cartilage explant cultures stimulated with IL-1+OSM were subjected to anion-exchange chromatography. The N-terminal sequence of the fragment of interest in the purified fractions was determined by automated Edman sequencing. Fetal bovine aggrecan was digested with full-length recombinant ADAMTS-4 and ADAMTS-5 and resulting degradation products were analyzed by sodium dodecyl sulfate/polyacrylamide gel electrophoresis (SDS/PAGE) and immunoblotting using an anti-G3 antiserum and an anti-neoepitope antibody that had been generated to the new N-terminus of the G3 fragment. RESULTS: Characterization of the 50-kDa fragment showed that it possesses chondroitin sulfate (CS) and is the result of a cleavage within the C-terminal portion of the CS-2 domain, adjacent to the G3 region. Sequence analysis identified the cleavage region as TQRPAE(2047)-(2048)ARLEIE, suggesting an aggrecanase-derived product. Using an anti-neoepitope antibody specific for the additional cleavage site, it was shown that the product is generated in vitro upon digestion of aggrecan by ADAMTS-5 and, to a much lesser extent, by ADAMTS-4. CONCLUSIONS: The abundance and rapid rate of release of this degradation product in organ cultures in the presence of OSM suggest that it could result from a unique aggrecan proteolysis mediated by aggrecanases.